Analisis Penerimaan Retribusi Laboratorium Terhadap PAD Pada Dinas Bina Marga Dan Bina Konstruksi Provinsi Sulawesi Selatan - Nurmayana, Sri; Nuraisyiah; Syachbrani, Warka (STIEM BONGAYA, 2025)
: This study aims to analyze laboratory retribution revenue at Dinas Bina Marga dan Bina Konstruksi Provinsi Sulawesi Selatan. The data collection technique used is documentation. The data analysis method applied in this study is descriptive quantitative analysis. The population consists of all reports on laboratory retribution revenue targets and realization, as well as Local Own-Source Revenue (PAD) reports. The sample includes reports on laboratory retribution revenue targets and realization, along with PAD reports from 2021 to 2023. The results show that laboratory retribution contributes significantly to Local Own-Source Revenue (PAD), with an average contribution of 79.8% over the past three years. The effectiveness of revenue collection is also considered very high, with an average realization rate of 132.56% of the target. Additionally, the efficiency level of retribution collection falls within the highly efficient category, with an average efficiency rate of 46.77%. These findings indicate that laboratory retribution still has the potential to be further optimized to maximize regional revenue.